Functional Hydrogel Dressings for Treatment of Burn Wounds - Shu, Wentao; Wang, Yinan; Zhang, Xi; Li, Chaoyang; Le, Hanxiang; Chang, Fei (Frontiers in Bioengineering and Biotechnology, 2021)
The therapy of burns is a challenging clinical issue. Burns are long-term injuries, and numerous patients suffer from chronic pain. Burn treatment includes management, infection control, wound debridement and escharotomy, dressing coverage, skin transplantation, and the use of skin substitutes. The future of advanced care of burn wounds lies in the development of “active dressings”. Hydrogel dressings have been employed universally to accelerate wound healing based on their unique properties to overcome the limitations of existing treatment methods. This review briefly introduces the advantages of hydrogel dressings and discusses the development of new hydrogel dressings for wound healing along with skin regeneration. Further, the treatment strategies for burns, ranging from external to clinical, are reviewed, and the functional classifications of hydrogel dressings along with their clinical value for burns are discussed.